2020
DOI: 10.1039/c9nj05246a
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surfactant in the sol–gel synthesis of CuO/TiO2 nanocomposites on its photocatalytic activities under UV-visible and visible light illuminations

Abstract: Effective and low-cost CuO/TiO2 nanocomposites were prepared at room temperature by a surfactant-assisted sol–gel method for photocatalytic activities under UV-visible and visible light irradiations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Many researchers [33] reported that adding surfactant could maintain stable suspension of particles. The surfactants play steric dispersing agent roles, which can keep particles in small diameters.…”
Section: Effects Of Hpc Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers [33] reported that adding surfactant could maintain stable suspension of particles. The surfactants play steric dispersing agent roles, which can keep particles in small diameters.…”
Section: Effects Of Hpc Surfactantmentioning
confidence: 99%
“…The surfactants play steric dispersing agent roles, which can keep particles in small diameters. [33] The surfactant can adsorb on TiO 2 surface, change its zeta potential to provide stability of the sol, and avoid the aggregation of particles. Two kinds of HPC were used as surfactants in this study, one with viscosity of 6-10 cps, and the other with viscosity of 150-400 cps.…”
Section: Effects Of Hpc Surfactantmentioning
confidence: 99%
“…Ravishankar [ 72 ] et al. reported the effect of surfactants on the photocatalytic performance of CuO/TiO 2 heterojunction materials prepared by the sol–gel method.…”
Section: Synthesis Of Nanoscale Spherical Tio2mentioning
confidence: 99%
“…Recent progress on coupling the heterogeneous structure of TiO 2 with visible light sensitizers has been demonstrated as a promising approach to substantially improve the light harvesting ability of the TiO 2 template. Several binary visible-light sensitizers, such as Bi 2 O 3 , Cu 2 O, CuO, Fe 2 O 3 , CdS, and Bi 2 S 3 , have been adopted for coupling with TiO 2 templates to achieve improved photoactive performance [2][3][4][5][6][7][8]. Among these visible-light sensitizers, binary oxides provide a better, more suitable process and chemical compatibility for integration with TiO 2 templates in comparison with most sulfides.…”
Section: Introductionmentioning
confidence: 99%